Investigation into a Link between Personal Resilience and Academic Achievement of English Education Study Program Students at State Islamic University in Sumatera, Indonesia - RATI MARTIANI (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2019)
This study was aimed at investigating the link between personal resilience and academic achievement. This study used correlational research method. 613 students of English Education Program Study in one state Islamic university in Palembang, South Sumatera were chosen as the population. Purposive sampling was used as a sampling technique which took 157 students as the sample. Furthermore, this study had two variables: students’ personal resilience and students’ academic achievement. The students’ personal resilience score was taken from questionnaire, while the students’ academic achievement in English was taken from their GPA documentation. The data was checked by using One Sample Kolmogrorov Smirnov Test by using SPSS to check whether the data were normal or not and for linearity, the data was checked by using One Way ANOVA Statistic analysis. From the data analysis, the correlation coefficient or the r-obtained (.211) was higher than r-table (0.1557). It means that p (0.0168) was higher than 0.05. In other words, there was significant link between students’ personal resilience and academic achievement. It implied that academic achievement was not affected by personal resilience dominantly.